Self-experienced virtual reality to improve balance reflexes in ice dancers. A pilot study - Tornese, D.; Botta, M.; Mattei, V.; Alpini, D. C. (Sport Sciences for Health, 2011)
The aim of the experiments was to use virtual reality stimulation to reweight visuovestibular sensory inputs in order to improve balance performances in ice dancers. In five athletes (three women and two men, mean age 22.5 years) from the Italian National Team rotational ocular reflexes were studied, both in the dark (rotational vestibuloocular reflex r-VOR) and in the light (rotational visuovestibuloocular reflex, r-VVOR). The athletes were rotated on a motorized chair and ocular reflexes were recorded by electrooculography. Skaters trained once a day for 20 days to maintain a one-leg stance on an oscillating platform during semi-immersion in a projected video acquired by a digital photocamera fixed to their head when they were skating. r-VOR gain increased significantly (p<0.001) in the three athletes with the lowest pretraining values. The virtual reality technique adopted is also as easy to perform in the usual training context, can be proposed as a low-cost well-tolerated approach also for specific training of patients with poor balance at least when oculomotor performance has to be optimized.